Using Singular in The Plural Sense (Study in the Quranic Verses and the Words of the Arabs) - Baso Pallawagau; Abdul Muiz Amir (Langkawi: Journal of The Association for Arabic and English, 2018)
This research deals with the placing of the singular in the meaning of the plural in the Quranic verses and the words of the Arabs. Hence, the problem of research is as follows: How did the linguists view the singular status of the plural? Was the use of singular in the meaning of the plural valid for all single words? The type of research used in this field is descriptive qualitative research, using the analytical method of grammar, and the technique of a collection consists of the library method. The result of the study answers this problem and that the advent of the singular in the meaning of the plural is not denounced by the Arabs if the speech is evidence of its collection. This method is mentioned in the Holy Quran and the words of the Arabs. However, not every single word is valid for the meaning of the plural without evidence